Strategi Komunikasi Pemasaran Dalam Menarik Minat Konsumen Untuk Menggunakan Jasa Pembiayaan Multiguna Bess Finance Di Kota Baturaja - Agustian, Herwandi; Purwitasari, Ira; Fathurrijal, Fathurrijal (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2021)
This study aims to determine marketing communication strategies in attracting customers to use Bess Finance multipurpose financing services. The research method used is descriptive qualitative. Data collection was carried out through observation, interviews, documentation and literature study. The in-depth interviews were conducted with 3 speakers who were internal parties of PT. Bess Finance which is directly related to the implementation of marketing communications at the service company and 2 customers who are domiciled in Palembang. Based on the analysis of the concept of the AIDA model, the results show that how the marketing process by introducing the services offered is able to influence customer interest in making decisions to trust and use Bess Finance multipurpose financing services.